Transparency, quality, and statistical consistency of meta-analytic systematic reviews in clinical child and adolescent psychology (2022–2024): study protocol for a meta-review - Magdalena Siegel; Selina Fanninger; Julia Riedel; Martina Zemp (Frontiers in Psychology)
Meta-analytic systematic reviews are crucial for advancing research and practice in Clinical Child and Adolescent Psychology (CCAP). Despite their importance, there has been no systematic investigation into transparency- and quality-related aspects of these reviews in leading CCAP journals. This study protocol (https://osf.io/qhrau/) proposes a meta-review to assess the transparency, methodological quality, and statistical consistency of recent meta-analytic systematic reviews (2022–2024) published in leading journals from CCAP, aiming to improve future practices in the field. We will include meta-analytic systematic reviews from seven leading journals publishing CCAP-related content between 2022 and 2024 (estimated sample size based on piloting = 60). Eligible systematic reviews need to have conducted a frequentist meta-analysis, define eligible populations as children or adolescents between 0 and 20 years (ideally based on primary study sample mean), may include a clinical psychological or psychotherapeutic intervention, and need to focus on clinical psychological outcomes (no comparators defined). We will search Web of Science (Core Collection) by combining journal names (fully indexed within this database) and systematic review-related keywords. Eligible meta-analytic systematic reviews will be assessed for transparency (PRISMA-adaptation; newly developed set of items for CCAP-related content), methodological quality (AMSTAR 2), and statistical consistency (statcheck). Descriptive analyses will include overall and domain-based scores, as well as exploratory analyses assessing associations with transparency-promoting factors on review and journal level. This meta-review can shed light on and enhance the transparency, quality, and statistical consistency within meta-analytic systematic reviews from the field of CCAP. In doing so, it may provide guidance for researchers, reviewers, and editors, while laying the groundwork for future meta-studies in this field.